Effect of a Hydroalcoholic Extract of Rosa сanina Flowers on Anxiety in Rats - Nemati, Z.; Komaki, A.; Shahidi, S.; Sarihi, A. (Нейрофизиология, 2015)
We investigated effects of the hydroalcoholic extract of Rosa сanina (dog rose) petals on behavior of rats in the elevated plus-maze (EPM) test; adult male Wistar rats weighing 200-240 g were used. Oral everyday administration of the Rosa extract in three doses (150, 300, and 450 mg/kg) was done for one week. Animal behavior in the EPM was videotaped for 10 min, and conventional indices considered to be related to the anxiety level were scored. Introduction of the Rosa canina extract significantly increased the number of open arm entries in a dose-dependent manner and also increased the time of stay in the open arms at a high dose (450 mg/kg). At the same time, the number of closed arm entries interpreted as a correlate of the locomotion intensity did not differ from the control at all doses. Thus, the Rosa canina extract, when orally administered, demonstrates an anxiolytic profile in rats. Future investigations are essential for better understanding of the anxiolytic properties of the extract and neurobiological mechanisms of its action (probable interactions of the Rose extract active agents with neurotransmitter systems.